Application of Electron Beam Melting (EBM) in Additive Manufacturing of an Impeller - Tan, Xipeng (2016)
An industrial impeller has been successfully fabricated by using Ti-6Al-4V ELI powder via a newly installed Arcam A2XX electron beam melting (EBM) machine. EBM was found to be preferable to build the circular or complex-shaped parts with thin walls. Several problems that frequently take place during the EBM fabrication are proposed based on the practical experience. It is found that metallization peeling-off, warpage, “swelling” and arc trips are the main reasons resulting in the failures of building jobs. It is suggested to pay close attention to the following aspects: a thorough cleanliness of the entire EBM system before start, a reasonable placement of builds on the start plate, an optimized design on geometries, etc., for a successfully built part.